Optimizing Information Management to Enhance Innovation in Administrative Services in High Schools - Arjiman (JIEMAN: Journal of Islamic Educational Management, 2026)
The rapid advancement of science, information, and communication technology has significantly transformed the education sector. In this context, implementing a Management Information System (MIS) is crucial for supporting effective data management and informed decision-making. However, administrative services at Madrasah Aliyah Negeri 1 Banyuwangi continue to face challenges, including complex procedures, inefficient data processing, and limited use of technology, which affect service quality and user satisfaction. This study aims to examine the optimisation of MIS in improving administrative service innovation, evaluate its effectiveness, and identify factors influencing its implementation. A descriptive qualitative approach with a phenomenological perspective was employed. Data were collected through participatory observation, semi-structured interviews, and documentation, and were analysed thematically. The findings indicate that MIS implementation has been systematically planned by integrating human resources, documentation, and technological tools. Its application through platforms such as EMIS, SIMPATIKA, RDM, AMS has improved data management and service delivery. Continuous evaluation further supports system refinement. Overall, MIS implementation enhances accuracy, efficiency, and service speed, while strengthening decision-making and promoting innovation in educational administration.